2005
DOI: 10.1016/j.matcom.2005.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Domain walls of single-component Bose–Einstein condensates in external potentials

Abstract: We demonstrate the possibility of creating domain walls described by a single component Gross-Pitaevskii equation with attractive interactions, in the presence of an optical-lattice potential. While it is found that the domain wall is unstable in an infinite system, we show that the external magnetic trap can stabilize it. Stable solutions also include "twisted" domain walls, as well as asymmetric solitons. The results apply as well to spatial solitons in planar nonlinear optical waveguides with transverse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Recall that, in the free space, the front solution exists at a single value of the propagation constant, k = 3/4, while an external potential may support a family of front solutions [26] (in Ref. [26], fronts were represented by solutions to the Gross-Pitaevskii equation which included the cubic nonlinearity and a sinusoidal potential). In the present model, it can be shown that front states may also be sustained by a single potential well, in the absence of the second channel.…”
Section: Basic Types Of Spatial Solitons In the Two-channel Systemmentioning
confidence: 99%
“…Recall that, in the free space, the front solution exists at a single value of the propagation constant, k = 3/4, while an external potential may support a family of front solutions [26] (in Ref. [26], fronts were represented by solutions to the Gross-Pitaevskii equation which included the cubic nonlinearity and a sinusoidal potential). In the present model, it can be shown that front states may also be sustained by a single potential well, in the absence of the second channel.…”
Section: Basic Types Of Spatial Solitons In the Two-channel Systemmentioning
confidence: 99%
“…In particular, it has been found that real 1D-version of Eq. (3) ψ xx + (ω − U(x))ψ − σψ 3 = 0 (4) with the model cosine potential U(x) = A cos 2x (5) describes bright and dark gap solitons [7,8,9,10], nonlinear periodic structures (nonlinear Bloch waves) [7,11], domain walls [12], gap waves [13] and so on. Some interesting relations between various nonlinear objects described by Eq.…”
Section: Introductionmentioning
confidence: 99%
“…The HH bifurcation has also been observed in other NLS-related settings. Several studies have demonstrated numerically the existence of "Krein collisions"-defined in section 5.3 below-in discrete wave equations [10,11,12,13] and in Bose-Einstein condensates (BEC) [14,15,16,17,18]. In these studies, and most others, the bifurcation is discussed only in the context of detecting the instability transition in the linear spectrum, or by performing a small number of numerical solutions to the initial value problem.…”
Section: Introductionmentioning
confidence: 99%